Annual variation in recruitment of freshwater mussels and its relationship with river discharge. Issue 4 (11th November 2015) - Ries, Patricia R.; Newton, Teresa J.; Haro, Roger J.; Zigler, Steven J.; Davis, Mike
Abstract: Vital rates such as mortality, growth, and recruitment are important tools to evaluate the status of threatened populations and identify their vulnerabilities, leading to enhanced conservation strategies. Native freshwater mussels are a guild of largely sedentary, filter‐feeding bivalves currently facing worldwide declines. Lack of recruitment has been identified as a major threat to mussel populations. A mussel bed in the Upper Mississippi River was sampled for 5 years (2008–2012). A trend analysis showed a significant decline in the percentage of species with juvenile representatives. Species were grouped into equilibrium and periodic life history strategies to assess past recruitment. Residuals from catch‐curve regressions quantified past year‐class strength of both strategists and Amblema plicata over a 13‐year period (1994–2006), and identified strong and weak year‐classes. Generalized linear regression models containing July maximum discharge and April minimum discharge explained 64% of the variation in recruitment strength of A. plicata . The best model for the equilibrium strategists explained 86% of the variation in recruitment and contained the same variables as A. plicata, but also incorporated the 7‐day minimum discharge. For the periodic strategists, the model containing the number of low‐flow pulses and the mean duration of high‐flow pulses explained 56% of the variation in recruitment strength. Understanding variation in recruitment dynamics of native mussels and its relationship to river discharge will be useful in designing effective management strategies to enhance conservation of this imperilled fauna. Copyright © 2015 John Wiley & Sons, Ltd.